Role of agricultural extension workers in horticultural agribusiness in Nusa Tenggara Timur Province, Indonesia - Leta, Rafael L. (Curtin University, 2002)
Despite the abundance of horticultural crops, farmers in the Nusa Tenggara Timur province of Indonesia (NTT) are still living under poverty level. The Indonesian government has identified agricultural extension workers as a 'point of spear' of agricultural development and given them 12 roles. Horticultural agribusiness would certainty be able to increase farmers' standard of living if agricultural extension workers can perform their roles effectively. However, in 1997, the average production of fruits was only 3.8 tonnes per hectare and 1.9 tonnes per hectare of vegetables. Ashraf (1993) has suggested that inefficiency of agricultural extension workers is one of the reasons why agricultural production does not improve to its full capacity. A study investigating the roles of Agricultural extension workers in horticultural agribusiness in Nusa Tenggara Timur (NTT) Indonesia was conducted. Interviews were conducted of 223 farmers, 46 agricultural extension workers and 32 government officers. A literature search suggests this is the first study ever done in Indonesia particularly in NTT which involved farmers, agricultural extension workers and government officers to investigate: 1) what roles were expected of agricultural extension workers by farmers, government officers and agricultural extension workers, 2) the perceptions of these groups about the effectiveness of agricultural extension workers in performing their roles, and 3) factors that impede agricultural extension workers' ability to perform their roles effectively. While the views of the three groups did not coincide, all three expected agricultural extension workers to use examples and demonstrations. All farmers expected agricultural extension workers to deliver extension in the right time.Both farmers and government officers expected agricultural extension workers to increase farmers' knowledge and skills, empower farmers and their group, and to be a part of farmers' community. Meanwhile, the roles of running activities that only deal with the agricultural activities, to support research recommendation, and to be the bridge between farmers and government were expected by government officers and agricultural extension workers. Farmers and agricultural extension workers have the same expectation for agricultural extension workers to transfer programs that suit. farmers' needs and problems, and to bring the programs as promised. The respondents perceptions about the effectiveness of agricultural extension workers in fulfilling their 12 roles were as follows: 1) farmers were dissatisfied with the roles for running plot demonstrations, program planning, using a brochure and running a field school; 2) agricultural extension workers were dissatisfied with the roles of making a brochure, running a field school, and delivering government projects; and 3) government officers were dissatisfied with the roles to encourage farmers' participation, finding and solving farmers' problems, agricultural extension workers as trainers, and running field schools. A Chi-square test found a significant difference between the groups in their perceptions of agricultural extension workers performance of their roles. The eight main constraints that impede agricultural extension workers' ability to perform their roles were the repeated restructuring of the Agricultural Department, low award or salary, lack of training, lack of transport, unclear job direction geographical conditions, lack of authority , and bureaucratic complexity.In conclusion, while the results of this study support the hypothesis that agricultural extension workers are not performing their roles effectively there are a number of reasons for this, many of them beyond the responsibility of agricultural extension workers. A key reason appears to be system failure. While the NTT province is supposedly following the Training and Visit model, very little effective training appears to be taking place and agricultural extension workers lack transport and other facilities to conduct effective visits and demonstrations. Another key deficiency is locally relevant research findings.